Targeted RNA sequencing reveals differential patterns of transcript expression in geographically discrete, insecticide resistant populations of Leptinotarsa decemlineata. Issue 7 (3rd May 2021) - Clements, Justin; Lamour, Kurt; Frost, Kenneth; Dwyer, James; Huseth, Anders; Groves, Russell L
Abstract: BACKGROUND: The Colorado potato beetle ( Leptinotarsa decemlineata Say) is a major agricultural pest of commercial potatoes, partially due to its ability to rapidly develop resistance to multiple insecticide modes of action. Patterns of L. decemlineata insecticide resistance in the contiguous United States have been linked to geographic location and regional management practices. Several previous studies have classified enzymes that are overexpressed following L. decemlineata exposure to commercial pesticides, many of which have been linked to xenobiotic metabolism. Studies have further associated geographic disparities in resistance patterns to cross‐resistance driven by fungicide exposure in the East Coast and Midwest. RESULTS: In this study, our objective was to investigate transcript expression of 38 previously classified detoxification enzymes induced by imidacloprid (an insecticide) and chlorothalonil (a fungicide) within five discrete populations of L. decemlineata obtained from areas in the USA representing eastern, midwestern and western production regions. We found unique patterns of transcript expression in different geographic locations, including overexpression of transcripts related to insecticide metabolism within insecticide‐resistant populations. CONCLUSION: The results suggest the genetic response of these populations may be partially linked to geographic location and corresponding management practices. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Median lethal dose assays and targeted RNA sequencing demonstrated that geographic location and management practices may influence transcript expression of insecticide resistance mechanisms in distinct populations Colorado potato beetles. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.